Susilo Bambang Yudhoyono’s Government Policy in Handling The Aceh Tsunami : a Historical Research - Agus Danugroho (Universitas Pancasakti Tegal, 2021)
Tsunami Aceh 2004 was one of the natural disasters whose status was designated as a national disaster in Indonesia. The event occurred compilation Indonesia does not yet have a special body and legislation governing natural disaster management. The Aceh tsunami has significant significance for the Indonesian community to the international level. The Aceh tsunami caused many complicated problems that had to be resolved by the Susilo Bambang Yudhoyono Government, among others, the regional government was unable to function properly, the disaster management law did not exist, supported international assistance in the military, and the National Budget was not available for the Aceh emergency response. The research objective in this study is about research conducted by the government of Susilo Bambang Yudhoyono in the 2004 tsunami in Aceh. The research method uses historical, heuristic, critical, interpretation, and historiographic methods. The results of this study are that the Government of Susilo Bambang Yudhoyono can resolve the problem by triggering regulations regarding the Law and the Special Body to handle problems that did not exist before.